Kelayakan Finansial Proyek Investasi Pengebunan Durian Merah Banyuwangi Secara Monokultur - et al, Agus Supriono (Universitas Katolik Santo Thomas Medan, 2025)
The germplasm of red durian from Banyuwangi Regency, East Java Province, began to be publicized in 1997 and later became widely known as 'Banyuwangi Red Durian'. Since its publication, a number of farmers have been observed cultivating it in monoculture plantations, particularly spread across the sub-districts of Glagah, Songgon, Licin, Kalipuro, and Giri. Therefore, it is quite interesting and important to conduct a financial feasibility study of the Banyuwangi Red Durian monoculture plantation investment project. The financial feasibility analysis was examined using 6 feasibility criteria: NPV, net B/C ratio, gross B/C ratio, PR, IRR, and PP. The economic life of the investment project was set at 30 years, based on a land area of one hectare, a planting distance of 10 x 10 meters, and seedlings originating from vegetative propagation (cuttings). It was estimated to begin yielding fruit (production) in the 6th year, with a discount rate of 9% per annum. Based on the analysis results, it was determined that, across all feasibility criteria, the Banyuwangi Red Durian plantation investment project per hectare is financially recorded as 'feasible'. Furthermore, based on a sensitivity analysis of the financial feasibility results, specifically by examining the NPV, gross B/C ratio, and IRR criteria, even if a decrease in production quantity and price levels by up to 30%, as well as an increase in fertilizer costs by up to 30%, are considered (assuming other factors remain constant), the Banyuwangi Red Durian monoculture plantation investment project is still deemed 'financially feasible'.